Análise da recuperação funcional no acidente vascular encefálico isquêmico após 30 dias de reabilitação em unidade pública de saúde - Aramaki, Roberta da Silva (2019)
Stroke is considered the third leading cause of death in adults worldwide and the first in Brazil, when considering cerebrovascular diseases. It is estimated that 75% of the cases must present some type of physical dependence and be removed from their work activities. After a neurological injury, changes occur in the brain in an attempt to recover from the damage - spontaneous biological recovery. Such changes are thought to occur in the first months and with greater intensity in the first month after the injury. In this period, it is extremely important that the individual is exposed to motor and sensory experiences, that is, a program of rigorous physiotherapy, so that it can potentiate functional recovery. This study aims to evaluate the impact of the physiotherapy program offered by a public health unit in the first 30 days after stroke. A total of 58 volunteers were selected, 30 of whom were not affected by stroke or any other incapacitating aggravating factor (Healthy Group - HG) and 28 individuals recruited within 48 hours after suffering stroke - selected within the neurology and emergency department of the Hospital de Clínicas da Universidade Federal of the Minas Gerais Triangle, and according to proper medical indication. The volunteers of the Stroke group were subdivided into two groups: CG - Control group, with 15 volunteers who received the physiotherapeutic treatment offered by the Clinical Hospital of the Federal University of the Triângulo Mineiro - in the post discharge period, each individual made his/her own decision regarding the subsequent treatment, without any intervention on the part of the researchers; IG - Intervention group, with 13 volunteers who underwent a complete program of physical therapy intervention based on the same Standard Operating Procedure (SOP) recommended to be followed by the professionals of the Clinical Hospital of the Federal University of Triângulo Mineiro - in the post-discharge period these individuals were submitted to rehabilitation sessions three times a week. The HG was evaluated in a single moment by the Fugl-Meyer and Wolf scales to serve as a parameter in the evaluation of the functional recovery of the CG and IG. The volunteers of the GC and GI were evaluated: 48 hours after the stroke, using the National Institute of Health Stroke Scale (NIHSS - USA), and Fugl-Meyer and Wolf scales; and after 15 days and 30 days, using the Fugl-Meyer and Wolf scales. All evaluations and the interventions on the IG were carried out by the same professional to minimize any bias. In the first evaluation (48 hours), GC and GI presented similar means. Subjects in the GS showed the following total mean Fugl-Meyer scores: 138.53 ± 2.14 (mean ± standard deviation). After 30 days, the subjects of the stroke groups presented a total score for the Fugl-Meyer scale equal to: 105.13 ± 21.12 (CG) and 129.46 ± 9.51 (IG). There is a clear improvement in the functional recovery of the GI in relation to the CG, approaching the scores of the GS. The Wolf scale assessment showed similar results. In the initial evaluation (48 hours) the CG and IG presented similar results, with greater difficulty to flex and abduct the shoulder for the accomplishment of various tasks (only 7 volunteers from each group were able to perform tasks that required these degrees of freedom). However, in the evaluation after 15 days, while no changes were observed in the CG, it was noticed a significant improvement in IG, with 11 (out of 12) individuals performing the requested tasks. In the third evaluation (30 days), the GI subjects improved their time to perform the tasks even more, while the subjects of the CG remained with difficulties for flexion and abduction of the shoulder. These results allow us to conclude that, starting from a similar baseline, after 30 days of intervention the GI showed a better functional recovery than the CG, approaching GS values. This fact indicates that the SOP recommended by the studied health unit, together with a functional rehabilitation protocol after discharge, can be effective for the functional recovery of stroke patients. However, the results perceived by the CG group demonstrate that there are significant deficiencies in the health care effectively offered to the victims of stroke by the public health unit where this work was performed